MANAJEMEN INSTITUSI PENDIDIKAN AGAMA ISLAM - Jaya; Muhammad Raihan Akbar; Rizqi Firmansyah; Wahyudin; Wahyu Kurniawan (STKIP Subang, 2026)
This study aims to conceptually analyze the management of Islamic religious educational institutions in implementing character education policies based on Islamic values ​​through a library research method. The study focuses on synthesizing various scientific literature regarding the application of four management functions: planning, organizing, implementing, and supervising, to support the effective implementation of character education policies. The results indicate that the success of Islamic religious educational institution management is determined by the institution's ability to integrate Islamic values ​​into institutional governance, curriculum development, student development, and the creation of a conducive academic culture. Synergy between institutional leaders, educators, education staff, and students is a crucial factor in creating an educational environment that supports Islamic character formation. Furthermore, an educational and ongoing monitoring system plays a role in maintaining consistent policy implementation. This study provides a theoretical contribution in the form of a conceptual model for Islamic religious educational institution management oriented towards strengthening institutional governance and character formation that is adaptive to the challenges of the digital era.